Analyzing Consumer Choices, the Impact of Job Motivation on Employee Performance - Ariesta, Rani (PRODUKTIF: Jurnal Kepegawaian dan Organisasi, 2023)
Success in improving performance and productivity must involve employees because employees are not only the main force in realizing change, but also increasingly actively participating in planning for change. The purpose of this research is to explain the influence of work motivation and burnout on employee performance at PT.Vinilon Building. This study uses quantitative research methods with data collection techniques through distributing questionnaires. The sample in this study is convenience sampling. Total respondents used in this study were 52 employee respondents. The data analysis technique used in this research is using multiple linear regression analysis techniques. As for the results of this study, namely the variables of work motivation and burnout variables have a significant impact on employee performance variables.